Holocene evolution of the east Texas coast and inner continental shelf: Along-strike variability in coastal retreat rates - Rodriguez, A. B.; Anderson, J. B.; Siringan, F. P.; Taviani, M. (Journal of Sedimentary Research, 2004)
The low gradient east Texas coast and inner-continental shelf, from Sabine Lake at the Texas-Louisiana border to the western end of Galveston Island, experienced extreme along-strike variations in rates of Holocene coastal retreat. Around 7.7 ka a barrier shoreline was located approximately 55 klm offshore. Toward the western end of Galveston Island, the shoreline retreated 55 km, occupying a position on the lagoon side of the Island by about 5.3 ka. Toward the Texas-Louisiana border, the shoreline retreated more gradually, occupying a position seaward of Sabine Bank by 5.3 ka. Between 4.7 ka and 2.8 ka the shoreline at Sabine Bank retreated -30 km, while Galveston Island prograded seaward. Bolivar Peninsula began to accrete around 1.5 ka. Heald and Sabine banks, located on the inner continental shelf above terraced fluvial deposits of the Trinity-Sabine incised valley, are the only preserved remnants of these former shoreline positions. Fluctuating rates of sea-level rise were not the forcing mechanism behind episodes of rapid shoreline retreat because these events were localized. Rather, along-strike variations in the rate of transgression were caused by the variable inner-shelf gradients, which increase towards the west, and the orientation of the Sabine incised valley and associated terraced fluvial deposits, which trend northeast-southwest (parallel to shore). As shorelines retreated over fluvial deposits, these served as local sand sources that enabled barrier islands to persist offshore, out of equilibrium with sea level. Once these sand sources became depleted, and/or sea level reached some critical threshold, barrier shorelines became stranded offshore as banks, and new shorelines formed landward. The geologic setting of coastal areas, specifically antecedent topography, plays a primary role in controlling coastal evolution. To accurately forecast long-term (centennial to millennial) coastal evolution, it is essential that impacts associated with variations in the underlying geology of coastal areas be incorporated into coastal forecasting models.
id: 2042; PT: J; UT: WOS:000221339900007